2015
DOI: 10.1016/j.plgene.2015.09.006
|View full text |Cite
|
Sign up to set email alerts
|

De novo transcriptome analysis to identify flavonoid biosynthesis genes in Stellera chamaejasme

Abstract: Stellera chamaejasme L. is a well-recognized traditional medicine in China and can synthesizes various secondary metabolites including a group of flavonoids. However, little is known about the molecular mechanisms underlying flavonoid biosynthesis. In this study, large-scale RNA sequencing on flower of S. chamaejasme produced a de novo transcriptome consisting of 32,216 unigenes with a N50 length of 1745 bp. Among all unigenes, 21,355 unigenes were identified as putative homologs of annotated sequences in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 21 publications
(20 reference statements)
1
3
0
Order By: Relevance
“…6), including two chalcone synthase (CHS), two chalcone isomerase (CHI), two flavanone 3-hydroxylase (F3H), five flavonoid 3'-hydroxylase (F3'H), two flavonoid 3',5'-hydroxylase (F3’5’H), four dihydroflavonol 4-reductase (DFR), four anthocyanidin synthase (ANS) and seven UDP-glucose flavonoid glucosyl transferase (UFGT). Aspects of the above ratios corroborate prior studies that have found comparatively high copy numbers for DFR ( Lotus japonicus [43]; cherries [44]; red leaf lettuce [45]), UFGT (columbines [46]; cherries [44]; Stellera chamaejasme [47]), F3H (peonies [48]), and ANS ( Zoysia [49]). Similarly, our finding of a low copy number for F3'5'H corroborates data from the above studies (one prominent exception is grapevines, which have been found to have exceptionally high copy variants of this enzyme [50]).…”
Section: Resultssupporting
confidence: 87%
“…6), including two chalcone synthase (CHS), two chalcone isomerase (CHI), two flavanone 3-hydroxylase (F3H), five flavonoid 3'-hydroxylase (F3'H), two flavonoid 3',5'-hydroxylase (F3’5’H), four dihydroflavonol 4-reductase (DFR), four anthocyanidin synthase (ANS) and seven UDP-glucose flavonoid glucosyl transferase (UFGT). Aspects of the above ratios corroborate prior studies that have found comparatively high copy numbers for DFR ( Lotus japonicus [43]; cherries [44]; red leaf lettuce [45]), UFGT (columbines [46]; cherries [44]; Stellera chamaejasme [47]), F3H (peonies [48]), and ANS ( Zoysia [49]). Similarly, our finding of a low copy number for F3'5'H corroborates data from the above studies (one prominent exception is grapevines, which have been found to have exceptionally high copy variants of this enzyme [50]).…”
Section: Resultssupporting
confidence: 87%
“…Before assembly, the raw reads with low quality (above 50% of bases with Q-value ≤ 20), ambiguous reads, adaptor sequences and duplication sequences were removed. A process of transcriptome assembly was described previously 37 . The transcriptome assembler, Trinity 38 , was performed by default parameters (K-mer = 25, group pairs distance = 400) with the following command: Trinity.pl–seqTypefq–left reads_1.fq–right reads_2.fq–max_memory 50 G–CPU 8.…”
Section: Methodsmentioning
confidence: 99%
“…Before RNA sequencing, the quality and quantity of total RNA were examined using an Agilent 2100 Bioanalyzer (Agilent, Santa Clara, CA, USA). The mRNA sequencing was constructed using previously described methods [ 32 ]. Briefly, total RNA were extracted and subsequently prepared for mRNA-Seq on the Illumina Genome Analyzer II following the manufacturer’s instructions (Illumina Inc., San Diego, CA, USA) and cDNA libraries were constructed using random hexamer primers and samples were sequenced using an Illumina HiSeq™ 2000 platform (Illumina Inc.).…”
Section: Methodsmentioning
confidence: 99%